Comparing the effects of total motion release® to stretching for increases in internal and external rotation at the shoulder - Sordello, N.; Bright, T.; Truesdell, T.; Puckett, J.; Baker, J. G.; Baker, R. T. (International Journal of Athletic Therapy & Training, 2021)
Focused Clinical Question: What are the effects of Total Motion Release® on shoulder range of motion compared with stretching in overhead athletes?